The responses of the gut microbiota to MBL deficiency. (June 2020) - Wu, Minna; Wang, Fanping; Yang, Jingwen; Li, Puze; Yan, Dong; Yang, Yonghui; Zhang, Wei; Ren, Jie; Zhang, Zhenchao; Wang, Mingyong
Highlights: Gut bacterial community composition in MBL −/− mice changed from that in WT mice. In MBL −/− mice, Akkermansia decreased, while Lactobacillus, Rikenella and Alistipes increased. Less interactions were observed between intestinal bacteria in MBL −/− mice. Some metabolic predicted genes, like "Immune system disease", increased in MBL −/− mice. Abstract: Mannose-binding lectin (MBL) deficiency is a common innate immune system deficiency, and is associated with exacerbations and increased colonization of some pathogens. However, the response of the gut microbiota, a pivotal factor in host health, to MBL deficiency is not clear. In this study, MBL −/− and wild-type (WT) mice were generated by backcrossing from MBL-A and MBL-C knockout (KO) mice, and fecal samples were collected at different ages (4th, 8th, 12th, 19th and 27th weeks). The gut microbiota was analyzed by high-throughput sequencing with universal 16S rDNA primers (V3-V5 region). The results showed that structural segregation of the gut microbiota occurred at the 8th, 12th, 19th and 27th weeks of age, although there were no significant differences in alpha diversities between MBL −/− and WT mice at different ages. Impressively, in MBL -/- mice, Akkermansia (from the family Verrucomicrobiaceae) were decreased significantly, Lactobacillus (from the family Lactobacillaceae) abundances, Alistipes and Rikenella (both from the family of Rikenellaceae) were always enriched. Network analysis showed that more interactions existed in the gut microbiota from WT mice (33 nodes and 70 edges) than in the gut microbiota from MBL -/- mice (23 nodes and 40 edges). The 16S rDNA function prediction results indicated that the abundances of predicted genes in the "immune system disease", "metabolic disease" and "nucleotide metabolism" pathways were significantly increased in the MBL -/- mice. In conclusion, this study revealed that the gut microbiota changed in MBL deficient mice, especially at ages older than 4 weeks.